The process of revitalization of culture and indigenous ethnic identity. The case of the Vepsian people in Karelia - Romanova, Evgenia (Universitetet i Tromsø, 2007)
This thesis is mainly focused on theoretical study of ethnicity and indigenousness, with some particular attention to language and politics. Some aspects of identity building and self-awareness among the Veps people living in Karelia are in focus. The study is interdisciplinary and thus also methodologically plural though the primary approach to ethnic identity is based on idea that ethnicity is socially constructed image. The actors of the revitalizing movement are nowadays engaged in the creation of ethnic markers, such as a common group name (Veps), elements of common culture and a common history (or a myth of common origin and the Finno-Ugric world). A discission about different symbols of ethnicity leads to the conclusion that the most urgent issue for the Veps is to preserve their dying-out language. And consequently, the language is only one marker of their distinctive culture in the modern globalized and urbanized milieu. But the gap between the ordinary people, official authorities and ethnic leaders in the area of language development is a reason of the continued effect of the assimilation processes among the Veps. The investigation is based on the fieldwork data collection conducted in the Republic of Karelia, Russia, in June-August 2005.